1998
DOI: 10.1073/pnas.95.19.11476
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots in cold adaptation: Localized increases in conformational flexibility in lactate dehydrogenase A4orthologs of Antarctic notothenioid fishes

Abstract: To elucidate mechanisms of enzymatic adaptation to extreme cold, we determined kinetic properties, thermal stabilities, and deduced amino acid sequences of lactate dehydrogenase A 4 (A 4 -LDH) from nine Antarctic (؊1.86 to 1°C) and three South American (4 to 10°C) notothenioid teleosts. Higher Michaelis-Menten constants (K m ) and catalytic rate constants (k cat ) distinguish orthologs of Antarctic from those of South American species, but no relationship exists between adaptation temperature and the rate at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
347
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(389 citation statements)
references
References 44 publications
37
347
1
4
Order By: Relevance
“…These results support the general hypothesis that alterations in protein conformational mobility can happen through one/few substitutions, providing insights into the evolutionary rates at which adaptive change may occur (43,44). They also indicate that a small change in the primary structure, namely a shortterm response, may be very efficient as such for generating an adaptive response to a challenge.…”
Section: Discussionsupporting
confidence: 80%
“…These results support the general hypothesis that alterations in protein conformational mobility can happen through one/few substitutions, providing insights into the evolutionary rates at which adaptive change may occur (43,44). They also indicate that a small change in the primary structure, namely a shortterm response, may be very efficient as such for generating an adaptive response to a challenge.…”
Section: Discussionsupporting
confidence: 80%
“…Similar covariation of k cat and K M has been observed previously in cold-adaptation of lactate-dehydrogenase A 4 (A 4 -LDH). It was shown that A 4 -LDH isolated from organisms living in colder habitats have increased K cat and K M values compared to A 4 -LDH isolated from organisms living in warmer habitats (42). Further K cat -versus-K M compensation has been observed for the oxidative DNA repair enzyme AlkB (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperthermophilic proteins are endowed with an extraordinary heat stability, as a consequence of a more tight compactness of the protein structure (Vieille and Zeikus, 2001). Vice versa, the psychrophilic counterparts possess an increased protein flexibility, which in most cases leads to a decreased stability compared to mesophilic proteins (D'Amico et al, 2006); in some psychrophilic enzymes the protein flexibility is enhanced in localized regions of the protein structure (Fields and Somero, 1998). Temperature adaptation of proteins is mostly relevant for the catalytic properties of the enzymes, as they must adapt the rate of the catalyzed reaction to the growth temperature of the organism.…”
Section: Introductionmentioning
confidence: 99%